Altered Functional Connectivity Within and Between Salience and Sensorimotor Networks in Patients With Functional Constipation - Duan, Shijun; Liu, Lei; Li, Guanya; Wang, Jia; Hu, Yang; Zhang, Wenchao; Tan, Zongxin; Jia, Zhenzhen; Zhang, Lei; von Deneen, Karen M.; Zhang, Yi; Nie, Yongzhan; et al. (Frontiers in Neuroscience, 2021)
Functional constipation (FCon) is a common functional gastrointestinal disorder; a considerable portion of patients with FCon is associated with anxiety/depressive status (FCAD). Previous neuroimaging studies mainly focused on patients with FCon without distinguishing FCAD from FCon patients without anxiety/depressive status (FCNAD). Differences in brain functions between these two subtypes remain unclear. Thus, we employed resting-state functional magnetic resonance imaging (RS-fMRI) and graph theory method to investigate differences in brain network connectivity and topology in 41 FCAD, 42 FCNAD and 43 age- and gender-matched healthy controls (HC). FCAD/FCNAD showed significantly lower normalized clustering coefficient and small-worldness. Both groups showed altered nodal degree/efficiency mainly in the rostral anterior cingulate cortex (rACC), precentral gyrus (PreCen), supplementary motor area (SMA), and thalamus. In FCAD group, nodal degree in the SMA was negatively correlated with difficulty of defecation, and abdominal pain was positively correlated with nodal degree/efficiency in the rACC which had a lower within-module nodal degree. Salience network (SN) exhibited higher functional connectivity (FC) with sensorimotor network (SMN) in FCAD/FCNAD, and FC between these two networks was negatively correlated with anxiety ratings in FCAD group. Additionally, FC of anterior insula (aINS)-rACC was only correlated with constipation symptom (i.e., abdominal pain) in FCNAD group. In FCAD group, FCs of dorsomedial prefrontal cortex-rACC, PreCen-aINS showed correlations with both constipation symptom (i.e., difficulty of defecation) and depressive status. These findings indicated the differences in FC of SN-SMN between FCAD and FCNAD, and it provides neuroimaging evidence based on brain function which portrays important clues for improving new treatment strategies.